Electro-Optic Spectral Switching in Multiline Optical Parametric Oscillators using Aperiodic Optical Superlattice Lithium Niobate - Wang, Tai Jie; Chung, Hung Pin; Deng, Lin Ming; Chang, Wei Kun; Pham, Tien Dat; Geiss, Reinhard; Pertsch, Thomas; Chen, Yen Hung (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We demonstrate an electro-optically switchable multi-wavelength optical parametric oscillator (OPO) based on an aperiodically poled LiNbO3 (APPLN). The OPO can radiate at 1540nm, 1550nm, or both wavelengths simply by switching the voltage on the APPLN.
CRIS-Team Scopus Importer:2023-04-20